Sosialisasi Aplikasi Android M-Magazine Solusi Sarana Mading SMA Negeri 5 Padang Selama Daring - Elfina Novalia; Apriade Voutama (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2022)
Abstract: Due to the Covid-19 pandemic, the teaching-learning process for the distribution of information at SMA Negeri 5 Padang is carried out online which has an impact on the learning process and information is not optimal and impressed. Basically, schools have a source of information which is usually called Mading School during online learning, the process of disseminating information is not optimally accepted by all students. The socialization was carried out by introducing and providing training on the M-Magazine application to students and school teachers which were carried out in a hybrid/semi-offline manner as a substitute for an Android-based school wall magazine. Service activities use the Waterfall model with several stages of activities systematically or sequentially in a hybrid manner, namely Semi online/offline with a series of activities, socializing the making of the M-Magazine application, training, and implementing the M-Magazine application directly to students and teachers. As a substitute for digital school bulletin boards and can be installed on Android Gadgets for every student and teacher so that the process of disseminating information can be carried out optimally without being hindered by place and time and can be used at any time.   Keywords: making school; online; m-magazine; mobile; android. Abstrak: Akibat Pandemi Covid19 proses belajar-mengajar penyaluran informasi Sekolah SMA Negeri 5 Padang dilakukan secara daring yang berdampak proses pembelajaran dan informasi tidak maksimal serta terkesan. Pada dasarnya Sekolah memiliki sumber informasi yang biasa disebut Mading Sekolah selama pembejaran daring berlangsung proses penyebaran informasi tidak maksimal diterima seluruh siswa. Sosialisasi dilakukan dengan memperkenalkan dan memberikan pelatihan tentang aplikasi M-Magazine kepada siswa dan guru Sekolah yang dilakukan secara hibrid/semi luring sebagaipengganti mading Sekolah berbasis Android. Kegiatan Pengabdian menggunakan model Waterfall dengan beberapa tahapan kegiatan secara sistematis atau berurutan secara hibrid yaitu Semi daring/luring dengan rangkaian kegiatan, sosialisasi pembuatan aplikasi M-Magazine, Pelatihan dan penerapan Aplikasi M-Magazine langsung kepada siswa dan guru. Sebagai pengganti sarana mading sekolah secara digital dan dapat diinstalkan di Gadget Android setiap Siswa dan Guru sehingga proses tersebarnya informasi dapat dilakukan secara maksimal tanpa terhalang tempat dan waktu dan dapat digunakan kapan saja.Kata kunci: mading sekolah; daring; m-magazine; mobile; android.